IMPLEMENTASI MANAJEMEN SEKOLAH DALAM MENINGKATKAN MUTU PENDIDIKAN DI MA YAPIA PARUNG - BOGOR - M. Musyaffa Halim; Nadya Kirana Putri; Novida Handayani; Sri Wahyuni (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
School management can be understood as all activities related to the arrangement of the educational process to achieve predetermined goals, which include short, medium, and long term goals. The main focus of this study is to explore how school management contributes to improving the quality of education by covering: (1) School program planning; (2) Implementation of school programs; and (3) Challenges faced. This study uses a qualitative approach with descriptive methods, and data collection is carried out through interview guidelines, observation, and documentation. The subjects studied were the principal, vice principal, teachers, school committee, students (optional) at MA Yapia Parung, Bogor Regency. From the results of the study it was found: (1) School program planning includes: teaching programs, which include: the need for the number of teachers and the division of teaching tasks, provision of textbooks, learning tools, teaching aids, procurement or development of school laboratories, procurement or development of school libraries, learning outcome assessment systems, and curricular activities; (2) Implementation of school programs is a strategy implemented to achieve improvements in the quality of education, which includes: program socialization, SWOT analysis, problem solving, quality improvement, and monitoring and evaluation of the implementation of school programs; and (3) Challenges in school program planning include the lack of community participation and economic difficulties, which reduce their support for management.